Prevalence of Lateral Epicondylitis Among Computer Users - Tehreem Mukhtar; Muhammad Salman Bashir; Rabiya Noor (Journal Riphah College of Rehabilitation Sciences, 2018)
Background: Lateral epicondylitis is an overuse injury involving the origin of common extensor tendon at elbow joint. Among computer users there is common complaint in neck, elbow and wrist region pain.